2008
DOI: 10.1091/mbc.e07-12-1289
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiaeRot1 Is an Essential Molecular Chaperone in the Endoplasmic Reticulum

Abstract: Molecular chaperones prevent aggregation of denatured proteins in vitro and are thought to support folding of diverse proteins in vivo. Chaperones may have some selectivity for their substrate proteins, but knowledge of particular in vivo substrates is still poor. We here show that yeast Rot1, an essential, type-I ER membrane protein functions as a chaperone. Recombinant Rot1 exhibited antiaggregation activity in vitro, which was partly impaired by a temperature-sensitive rot1-2 mutation. In vivo, the rot1-2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…2). The calculated molecular weight of Kre6 is 80,122, but the detected Kre6 is significantly larger than the expected size, probably because of N-glycosylation and phosphorylation (3,12). We concluded a specific antiKre6 antiserum was obtained that specifically recognizes Kre6 but not Skn1.…”
Section: Chromosome-encoded Kre6-3ha Is Strongly Detected At the Sitementioning
confidence: 78%
See 2 more Smart Citations
“…2). The calculated molecular weight of Kre6 is 80,122, but the detected Kre6 is significantly larger than the expected size, probably because of N-glycosylation and phosphorylation (3,12). We concluded a specific antiKre6 antiserum was obtained that specifically recognizes Kre6 but not Skn1.…”
Section: Chromosome-encoded Kre6-3ha Is Strongly Detected At the Sitementioning
confidence: 78%
“…The loss of Rot1 in the ER results in a severe growth defect and reduction of the cell wall ␤-1,6-glucan content. Takeuchi et al (12) showed that Rot1 functions as the molecular chaperon of Kre6 and Kre5 and is engaged in the folding and stabilization of these proteins. They suggested that the reduction of the ␤-1,6-glucan content in the ⌬rot1 cells may be a secondary effect through the defect of Kre6 and Kre5 (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Glc 3 Man 9 GlcNAc 2 glycan, which comprises the N-linked core, is rapidly processed by glucosidase I (Gls1/ Cwh41) and glucosidase II (Gls2/Rot2) enzymes to remove the three terminal glucose residues and generate Man 9-GlcNAc 2 . Molecular chaperones collaborate in protein folding during these glucose-trimming events and Rot1 alone has been shown to possess a general chaperone activity (Takeuchi et al 2008). In many cell types, a calnexindependent folding cycle operates to iteratively fold and monitor polypeptide status through the coordinated activities of glucosidase I, glucosidase II, UDP-glucose;glycoprotein glucosyltransferase (UGGT), and calnexin (Cne1).…”
Section: Glucosidase Mannosidase Trimming and Protein Foldingmentioning
confidence: 99%
“…In addition, the sec 59-1 phenotype could be rescued by overexpression of the ROT1 gene, encoding the endoplasmic reticulum Rot1 protein. The latter is implicated in cell wall biogenesis and acts as a chaperone for misfolded proteins [36,37]. Recently, we have shown also that Rot1 interacts with Ost3, one of the nine subunits of the oligosaccharyltransferase complex, the key enzyme of N-glycosylation.…”
Section: Cell Wall Alteration Resulting From the Defect In Dolichol Amentioning
confidence: 97%